2019
DOI: 10.1016/j.euroneuro.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical effects of oxytocin in people at clinical high risk for psychosis

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 89 publications
1
15
0
Order By: Relevance
“…While this study demonstrated that acute OT administration modulates key brain regions during inferring others' social emotions, OT effects on functional outcomes in CHR-P subjects need to be tested in future longer-term clinical trials. Furthermore, in terms of the neurophysiological mechanisms by which OT has its effects, we previously reported that OT modulates cerebral (hippocampal) perfusion in CHR-P patients 35 , but did not appear to modulate regional concentrations of neurochemical metabolites 36 . The mechanisms by which OT increases neural efficiency in CHR-P individuals therefore warrants further research.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…While this study demonstrated that acute OT administration modulates key brain regions during inferring others' social emotions, OT effects on functional outcomes in CHR-P subjects need to be tested in future longer-term clinical trials. Furthermore, in terms of the neurophysiological mechanisms by which OT has its effects, we previously reported that OT modulates cerebral (hippocampal) perfusion in CHR-P patients 35 , but did not appear to modulate regional concentrations of neurochemical metabolites 36 . The mechanisms by which OT increases neural efficiency in CHR-P individuals therefore warrants further research.…”
Section: Discussionmentioning
confidence: 96%
“…Intranasal OT administration followed recommended guidelines and a protocol adopted by a previous study conducted at our institute 49 . As done in our previous studies 35,36 , participants self-administered one puff (4 IU) of intranasal OT or matched placebo every 30 s, alternating between nostrils, until 40 IU had been administered. See refs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were randomly allocated to a treatment order (oxytocin/placebo or placebo/oxytocin). After drug administration, participants were guided to a magnetic resonance imaging (MRI) scanner (data already reported 47,78 or to be reported in forthcoming publications). During the MRI session, we acquired, in the following order, two arterial spin-labelling resting-state scans, two runs of BOLD fMRI during a theory-of-mind task 79 , then two structural scans (T1 and FLAIR), a resting-state BOLD fMRI and a magnetic resonance spectroscopy scan at the end.…”
Section: Study Design and Procedures Chr-p Samplementioning
confidence: 99%
“…In contrast with schizophrenia, the number of intranasal oxytocin studies conducted with people at CHR-P until now is surprisingly scarce. We have previously shown that a single acute dose of intranasal oxytocin (40 IU) modulates hippocampal perfusion (a key element of our current models of the neurobiological mechanisms underlying the onset of psychosis) 45 47 and increases the levels of choline in the anterior cingulate cortex of men at CHR-P 48 . However, while oxytocin has long been recognised for its roles in the regulation of the cardiovascular and ANSs 49 51 , we are still unclear about whether intranasal oxytocin might address the ANS dysfunction observed along the psychosis spectrum.…”
Section: Introductionmentioning
confidence: 99%